Analysis Of Banking Financial Ratios As A Measurement Of Financial Performance In PT. Mandiri Bank, Tbk - Ainaya Tazriah; Aliah Pratiwi (INVOICE : JURNAL ILMU AKUNTANSI, 2023)
This research aimed to assess the financial performance of PT. Bank Mandiri, Tbk using banking financial ratios as indicators. It relied on secondary quantitative data, including BI Current Accounts, Total Credit, Total Assets, Total Debt, Total Equity, Long Term Debt, and Net Profit at PT. Bank Mandiri, Tbk. The study encompassed a 23-year period, from 1998 to 2021, since the company's listing on the IDX. However, the analysis focused on a 10-year sample, specifically from 2012 to 2021, chosen through purposive sampling with criteria set by Sugiyono (2016), including the latest financial report data and data available for 10 consecutive years (2012-2021). Data collection methods involved documentation and literature study, concentrating on balance sheets and income statements of PT. Bank Mandiri, Tbk from 2012 to 2021. The analysis examined various financial ratios, such as Reserve Requirement (RR), Loan To Asset Ratio (LAR), Debt To Equity Ratio (DER), Long Term Debt To Asset Ratio (LDAR), Return On Assets (ROA), and Return On Equity (ROE). The statistical analysis employed a one-sample t-test using SPSS version 21. The findings indicated that PT. Bank Mandiri, Tbk exhibited good financial performance in terms of RR, LAR, LDAR, and ROA. However, it showed less favorable results for DER and ROE, suggesting areas for improvement in the company's financial management and strategies.